KAJIAN HUKUM LEMBAGA PERKREDITAN DESA (LPD) DI BALI DALAM TINJAUAN KEDUDUKAN DAN PERANNYA - I Made Widana (Nusantara Hasana Journal, 2023)
One of the financial institutions in the village that has survived to this day and is moving to alleviate difficulties in the village and was formed by the village community itself, one of which is the Village Credit Institution which is a financial business entity belonging to a Balinese traditional village and carries out business activities in a traditional village environment. unfortunately, the existence of LPDs is a problem from the existence of regulations that require Village Credit Institutions to become Village Credit Banks in accordance with Article 58 of Law Number 10 of 1989 concerning Banking besides that LPDs are also regulated in Law Number 1 of 2013 concerning Microfinance Institutions which provides space for the LPD to be recognized based on customary law. In this case the author raises the issue of how to study the law of the Village Credit Institution (LPD) in Bali in a review of its position and role. This writing uses a normative juridical approach based on primary data, namely laws relating to writing, secondary data in the form of books, journals and the results of previous research. From the results of a normative juridical approach, the existence of LPDs cannot be equated with Rural Banks because the existence of LPDs belonging to the adat village of Bualu has been recognized based on customary law in the LKM Law as well as in Article 18A, Article 18B, and Article 28I of the 1945 Constitution. it has been regulated in which the state recognizes and respects customary law community units along with their traditional rights as well as cultural identities and traditional community rights are respected in line with the development of times and civilization, and is regulated in TAP MPR Number IX of 2001, Law Human Rights, Local Government Act. Laws on MFIs, Village Laws and Bali Province Regional Regulations.